Altered development in GABA co‐release shapes glycinergic synaptic currents in cultured spinal slices of the SOD1G93A mouse model of amyotrophic lateral sclerosis. (27th May 2016) - Medelin, Manuela; Rancic, Vladimir; Cellot, Giada; Laishram, Jummi; Veeraraghavan, Priyadharishini; Rossi, Chiara; Muzio, Luca; Sivilotti, Lucia; Ballerini, Laura
Abstract : Key points: Increased environmental risk factors in conjunction with genetic susceptibility have been proposed with respect to the remarkable variations in mortality in amyotrophic lateral sclerosis (ALS). In vitro models allow the investigation of the genetically modified counter‐regulator of motoneuron toxicity and may help in addressing ALS therapy. Spinal organotypic slice cultures from a mutant form of human superoxide dismutase 1 (SOD1G93A) mouse model of ALS allow the detection of altered glycinergic inhibition in spinal microcircuits. This altered inhibition improved spinal cord excitability, affecting motor outputs in early SOD1 G93A pathogenesis. Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal, adult‐onset neurological disease characterized by a progressive degeneration of motoneurons (MNs). In a previous study, we developed organotypic spinal cultures from an ALS mouse model expressing a mutant form of human superoxide dismutase 1 (SOD1 G93A ). We reported the presence of a significant synaptic rearrangement expressed by these embryonic cultured networks, which may lead to the altered development of spinal synaptic signalling, which is potentially linked to the adult disease phenotype. Recent studies on the same ALS mouse model reported a selective loss of glycinergic innervation in cultured MNs, suggestive of a contribution of synaptic inhibition to MN dysfunction and degeneration. In the present study, we further exploit organotypic cultures from wild‐type and SOD1 G93A mice to investigate the development of glycine‐receptor‐mediated synaptic currents recorded from the interneurons of the premotor ventral circuits. We performed single cell electrophysiology, immunocytochemistry and confocal microscopy and suggest that GABA co‐release may speed the decay of glycine responses altering both temporal precision and signal integration in SOD1 G93A developing networks at the postsynaptic site. Our hypothesis is supported by the finding of an increased MN bursting activity in immature SOD1 G93A spinal cords and by immunofluorescence microscopy detection of a longer persistence of GABA in SOD1 G93A glycinergic terminals in cultured and ex vivo spinal slices. Key points: Increased environmental risk factors in conjunction with genetic susceptibility have been proposed with respect to the remarkable variations in mortality in amyotrophic lateral sclerosis (ALS). In vitro models allow the investigation of the genetically modified counter‐regulator of motoneuron toxicity and may help in addressing ALS therapy. Spinal organotypic slice cultures from a mutant form of human superoxide dismutase 1 (SOD1G93A) mouse model of ALS allow the detection of altered glycinergic inhibition in spinal microcircuits. This altered inhibition improved spinal cord excitability, affecting motor outputs in early SOD1 G93A pathogenesis.